ANALISIS PERUBAHAN PENGGUNAAN LAHAN TERHADAP PERUBAHAN ZONA NILAI TANAH DI KECAMATAN MAPANGET KOTA MANADO PROVINSI SULAWESI UTARA - Ricky Hot Ropanda Marolop Tua Hamonangan Sihotang; Leonardus Ricky Rengkung; Theodora Maulina Katiandagho (Sam Ratulangi University, 2021)
This research aims to describe land use changes and land value zone changes, analyze land use changes to land value zone changes from 2014 to 2019, and predict land use changes for 5 (five) years from 2020 to 2025 in Mapanget District. The analytical methods used in this research are spatial analysis and trend analysis. The results showed that changes in land use increased and decreased, while changes in land The results showed that there was an increase and decrease in land use change, while changes in land value increased every year, land use changes did not directly affect land values because they were influenced by internal and external factors, and the results of land use predictions increased for land use changes. settlements and offices & trade as well as decreased land use for changes in agricultural land use in Mapanget District.